2012
DOI: 10.1136/bjsports-2012-091303
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical significance of sonographic tendon abnormalities in asymptomatic ballet dancers: a 24-month longitudinal study

Abstract: The presence of sonographic abnormalities is common in ballet dancers, but only the presence of focal hypoechoic changes predicts the development of future tendon-related disability. This suggests that screening of asymptomatic individuals may be of use in identifying those who are at higher risk of developing tendon-related disability, which may in turn allow targeted modifications of training or other preventative regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 25 publications
10
110
2
7
Order By: Relevance
“…In turn, clinically asymptomatic individuals may commonly exhibit sonographic abnormalities in the Achilles and patellar tendons, especially amateur or professional athletes (31); accordingly, US as well as PD exhibit a high rate of both false-negative and false-positive findings. Moreover, there is only a poor to moderate between-reader correlation with regard to the detection of structural (Bmode) changes (32).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, clinically asymptomatic individuals may commonly exhibit sonographic abnormalities in the Achilles and patellar tendons, especially amateur or professional athletes (31); accordingly, US as well as PD exhibit a high rate of both false-negative and false-positive findings. Moreover, there is only a poor to moderate between-reader correlation with regard to the detection of structural (Bmode) changes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that individuals with non-symptomatic tendinopathies are included in our healthy tendon group. However, the prevalence of asymptomatic tendinopathy is relatively low in active young adults (3.8 %, Joseph et al, 2012) and the ability of imaging techniques to predict future symptomatic tendinopathy has also been questioned (Comin et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…These changes typically occur in the middle third of the tendon (known as the critical zone), particularly medially, and this portion of the tendon is the most poorly vascular [29]. Recent studies using ultrasound of the Achilles have shown that intratendinous hypoechoic areas in asymptomatic ballet dancers [30] or areas of abnormal neovascularity or tendon thickening in asymptomatic runners [31] may be predictive of future symptoms with continued sporting activity.…”
Section: Biomechanics/ Mechanism Of Injurymentioning
confidence: 99%